Publicidad formal de servicios inmobiliarios en Bogotá y Latinoamérica, ¿otro “termómetro” del crecimiento urbano? - Peña Barrera, Carlos Roberto (El Colegio de México A.C., 2011)
The main objects of this research are given below: 1) prove the hypothesis that city growth can also be measured by using the analysis of data extracted from real estate companies’ advertisements, published in the paper and on-line versions of the Yellow Pages; 2) compare the results of these data with population, housing, urban area, GDP and real estate land census figures. To this end, data were obtained from the Bogotá directory for the years that permitted a comparison between the dates when the last population and housing censuses (1993 and 2005) were carried out and 2008, to provide a more recent overview. Data were also taken from the virtual Yellow Pages of certain major Latin American cities in 2009. In the case of Bogotá, urban growth proved to be directly proportional to the number of real estate firms, as it did in a number of Latin American cities. In short, analyzing these data is an important means of measuring urban growth at least for the last two decades. It is also an innovative indicator for monitoring the growth of many cities in the world that publish virtual Yellow Pages.